PENGARUH KUALITAS PELAYANAN DAN NILAI PELANGGAN TERHADAP KEPUASAN PENGUNJUNG TEMPAT WISATA HAIROS WATERPARK MEDAN - Apriandi Sembiring; Sri Rezeki (Jurnal PLANS : Penelitian Ilmu Manajemen dan Bisnis, 2017)
This research aims to determine the effect of Service Quality and Customer Value at the Visitor Satisfaction  at Hairos Waterpark Medan. Based on the results of pre-study to do an interview to Manager Hairos Waterpark Medan, the population in this study is that consumers who visit with the average number of 3,468 per month. Accindental sampling using sampling with a sample of 97 people visitors .The test used is the test data quality and classical assumption. The hypothesis test uses multiple linear regression analysis, f test and t test. Validity of test results obtained t> t table for each item reliability test questions and questionnaires obtained a Cronbach alpha of each variable is 0.792 for the variable X1, 0.698 for X2 and 0.605 for the variable Y. This value is greater than the level that is significantly rtabel 0.361. The data analysis of each variable regression equation Y = 9.618 + 0.256 X1 + 0.216 X2 + e. Retrieved R2 of 0.234, which means the X1 and X2 explain the effect on variable Y by 23.4% while the remaining 76.6% is explained variables outside the company. The resulting partial test each independent variables affect the dependent variable with research significance less than 0.05, and the results of the test-simultaneous calculation of 14.369 with Ftable 3.09 which means Fresult> F table with a level of significant (α) 0,000 <0, 05, which means that the hypothesis is accepted that the quality of service and customer value together significant effect on visitor satisfaction hairos waterpark attractions terrain. Keyword : Service Quality, Customer Value, Visitor Satisfaction